Rekonstruksi Regulasi Perlindungan Konsumen ASEAN: Studi Perbandingan Indonesia Dan Singapura - Kelsha Berliana Rifty (Jurnal Kajian Ilmiah, 2026)
This article examines consumer protection in cross-border e-commerce, focusing on Indonesia, Singapore, and  China.  The  rapid  growth  of  digital  commerce across borders poses significant challenges for national legal systems in   safeguarding   consumer   rights   effectively.   This   study employs  a  normative  juridical  approach  with  qualitative-comparative analysis, exploring relevant  legislation,  policies, and  law  enforcement  practices  in  the  three  countries.  The findings  reveal  that  Singapore  has  established  the  most comprehensive consumer protection legal framework, closely aligned   with   international   standards.   China   utilizes   a centralized   regulatory   model   that   emphasizes   platform liability, resulting in stricter oversight of digital transactions. In contrast, Indonesia struggles with fragmented regulations, limited policy integration, and weak law enforcement, leading to  less  effective  consumer  protection  in  cross-border  e-commerce.    The    study    concludes    that    harmonizing international consumer protection standards and strengthening   national   law   enforcement   are   crucial   to addressing   the   challenges   of   cross-border   e-commerce. Enhanced  regulatory  cooperation  and  improvedconsumer digital   literacy   are   also   necessary   to   ensure   effective protection in digital markets